Does environmental science crowd out non-epistemic values?. (June 2021) - Gillette, Kinley; Inkpen, S. Andrew; DesRoches, C. Tyler
Abstract: While no one denies that science depends on epistemic values, many philosophers of science have wrestled with the appropriate role of non-epistemic values, such as social, ethical, and political values. Recently, philosophers of science have overwhelmingly accepted that non-epistemic values should play a legitimate role in science. The recent philosophical debate has shifted from the value-free ideal in science to questions about how science should incorporate non-epistemic values. This article engages with such questions through an exploration of the environmental sciences. These sciences are a mosaic of diverse fields characterized by interdisciplinarity, problem-orientation, policy-directedness, and ubiquitous non-epistemic values. This article addresses a frequently voiced concern about many environmental science practices: that they 'crowd out' or displace significant non-epistemic values by either (1) entailing some non-epistemic values, rather than others, or by (2) obscuring discussion of non-epistemic values altogether. With three detailed case studies – monetizing nature, nature-society dualism, and ecosystem health – we show that the alleged problem of crowding out emerges from active debates within the environmental sciences. In each case, critics charge that the scientific practice in question displaces non-epistemic values in at least one of the two senses distinguished above. We show that crowding out is neither necessary nor always harmful when it occurs. However, we do see these putative objections to the application of environmental science as teaching valuable lessons about what matters for successful environmental science, all things considered. Given the significant role that many environmental scientists see for non-epistemic values in their fields, we argue that these cases motivate lessons about the importance of value-flexibility (that practices can accommodate a plurality of non-epistemic values), transparency about value-based decisions that inform practice, and environmental pragmatism. Highlights: This article addresses a concern that the environmental sciences 'crowd out' or displace significant non-epistemic values. We analyze three active debates (monetizing nature, nature-society dualism, ecosystem health) where this concern emerges. We argue that crowding out is neither necessary nor always harmful when it occurs. However, this concern does illuminate lessons about what matters for successful environmental science, all things considered.